A study of the publication exchange program of selected academic libraries in Metro Manila problems and issues - Garvilles, Jesserylle G. (2005)
This study was conducted to examine the existing publication exchange program among selected academic libraries in Metro Manila and to determine the problems and issues encountered by the librarians in the processes and procedures of exchanges. To do this, the factors that affect the publication exchange program were closely analyzed - sources of funds, the qualities of institutions' publications send and received, and the support it have from the university and college administration.